1986
DOI: 10.1002/ana.410200403
|View full text |Cite
|
Sign up to set email alerts
|

Locus ceruleus lesions and eosinophilic inclusions in MPTP‐treated monkeys

Abstract: Systemic administration of the recently discovered neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) produces severe clinical parkinsonism and degeneration of the substantia nigra in humans and monkeys. In previous studies, no convincing structural damage to nerve cells outside the substantia nigra could be demonstrated in subhuman primates. Using a protracted MPTP regimen and older animals, we now report locus ceruleus lesions and eosinophilic inclusion bodies in squirrel monkeys. The inclusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 321 publications
(123 citation statements)
references
References 25 publications
3
118
0
2
Order By: Relevance
“…However, a chronic model with implanted osmotic pumps delivering constant small amounts of the toxin would have been a more optimal model to mimic the disease (385). Despite prolonged administration, however, MPTP does not generate Lewy bodies (76), although it has been described in a few cases (386,387). In line with this, intracytoplasmic inclusions were not observed in our model.…”
Section: Mptp Model Of Pdsupporting
confidence: 87%
“…However, a chronic model with implanted osmotic pumps delivering constant small amounts of the toxin would have been a more optimal model to mimic the disease (385). Despite prolonged administration, however, MPTP does not generate Lewy bodies (76), although it has been described in a few cases (386,387). In line with this, intracytoplasmic inclusions were not observed in our model.…”
Section: Mptp Model Of Pdsupporting
confidence: 87%
“…One possibility is that basal ganglia function differs between species. However, although it was initially reported that MPTP did not cause LC cell death in nonhuman primates, it has now become clear that typical nonhuman primate MPTP regimens nearly always result in LC cell death and/or loss of NE from terminal fields (28)(29)(30)(31)(32)(33)(34). In contrast, typical MPTP dosing regimens cause profound DA depletion with little effect on LC neurons or NE content in mice (10,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…This specific and reproducible neurotoxic effect to the nigrostriatal system is a strength of this model. Although intraneuronal inclusions reminiscent of Lewy bodies have been described in MPTP-injected monkeys (Forno et al 1986), in general, this pathological feature is absent in mice. However, it has been claimed that when mice are infused with a chronic low dose of MPTP over a period of 30 d using osmotic minipumps, inclusions immunoreactive for both ubiquitin and a-synuclein can be detected (Fornai et al 2005).…”
Section: K Tieumentioning
confidence: 99%